(untitled) (Research, Society and Development, 2021)
The Arecaceae family, acknowledged worldwide for its economic and environmental importance, faces sharp decline in population due, mainly, to anthropogenic action. This work consists of a wide review of the scientific publications on the family and, more specifically, of the genera Butia (Becc,) Becc. and Syagrus Mart. Here we gather, organize and compile botanical characteristics and biogeographic aspects of the mentioned genera, and we did it aiming to support research work on viable alternatives for the conservation of these palm trees and meeting the market demands for seedlings of these tropical species. A proposed alternative is the development of hybridization methodologies between these two genera, in order to obtain desirable answers for the commercial purpose. And, at the same time, implement conservation plans for native palm populations. The data collected were obtained from scientific literature on websites and magazines, from June 2019 to March 2021. The searches involved works from 1970 to 2021. In this exploratory research, it is important to emphasize the pivotal role regarding interpretation and the opinions of the researchers, in such a way that it is possible to integrate them into the works, providing a theoretical foundation that supports a discussion about the proposed theme.